Sulfonic acid covalently grafted halloysite nanotubes for highly efficient synthesis of biofuel 5-ethoxymethylfurfural. Issue 9 (14th April 2022) - Xiang, Yanping; Zhao, Kangyu; Zhou, Shuolin; Zhao, Wenguang; Zeng, Zhijuan; Zhu, Xiaoting; Liu, Xianxiang
Abstract : The sulfonic acid grafted halloysite nanotubes (HNTs-SO3 H) exhibited excellent catalytic activity in the synthesis of biofuel 5-ethoxymethylfurfural from biomass-derived 5-hydroxymethylfurfural. Abstract : The catalytic transformation of biomass derived compounds into valuable liquid fuels has received considerable attention in the past few years. In this work, sulfonic acid grafted halloysite nanotubes (HNTs-SO3 H) were facilely synthesized via functionalizing the halloysite nanotubes with 1, 3-propanesultone, and the physico-chemical properties of the synthesized catalysts were analyzed by Fourier transform infrared spectroscopy (FT-IR), transmission electron microscopy (TEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), N2 adsorption isotherm techniques, etc. The characterization results revealed that the organic–inorganic mesoporous materials preserved the tubular structure of the halloysite nanotubes and were equipped with active sulfonic acid sites. The as-synthesized catalyst was employed for the catalytic conversion of 5-hydroxymethylfurfural (HMF) to biofuel 5-ethoxymethylfurfural (EMF) under solvent-free conditions. Response surface methodology (RSM) with Box–Behnken design (BBD) was used to investigate the influence of the reaction conditions such as reaction temperature, reaction time and catalyst dosage on EMF yield. An excellent EMF yield of 86.4% and HMF conversion of 99.3% could be achieved at 126 °C for 35 minutes over the HNTs-SO3 H catalyst. Furthermore, the kinetics of the conversion of HMF to EMF was also studied, and the kinetic modeling results indicated that this reaction follows pseudo-first-order kinetics, and the activation energy obtained was 60.12 kJ mol −1 .